(10Z)-Debromohymenialdisine from Marine Sponge Stylissa sp. Regulates Intestinal Inflammatory Responses in Co-Culture Model of Epithelial Caco-2 Cells and THP-1 Macrophage Cells - Lee, Seon Min (Molecules, 2019)
Crohn’s disease (CD) and ulcerative colitis (UC), collectively referred to as inflammatory bowel disease (IBD), are autoimmune diseases characterized by chronic inflammation within the gastrointestinal tract. Debromohymenialdisine is an active pyrrole alkaloid that is well known to serve as a stable and effective inhibitor of Chk2. In the present study, we attempted to investigate the anti-inflammatory properties of (10Z)-debromohymenialdisine (1) isolated from marine sponge Stylissa species using an intestinal in vitro model with a transwell co-culture system. The treatment with 1 attenuated the production and gene expression of lipopolysaccharide (LPS)-induced Interleukin (IL)-6, IL-1β, prostaglandin E2 (PGE2), and tumor necrosis factor-α in co-cultured THP-1 macrophages at a concentration range of 1–5 μM. The protein expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 were down-regulated in response to the inhibition of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) translocation into the nucleus in cells. In addition, we observed that 1 markedly promoted the nuclear translocation of nuclear factor erythroid 2 related factor 2 (Nrf2) and subsequent increase of heme oxygenase-1 (HO-1) expression. These findings suggest the potential use of 1 as a pharmaceutical lead in the treatment of inflammation-related diseases including IBD.